Housing type and risk of malaria among under-five children in Nigeria: evidence from the malaria indicator survey (2018)
Background: Malaria remains one of the major causes of morbidity and mortality among under-five (U5) children in Nigeria. Though different environmental factors have been assessed to influence the distribution and transmission of malaria vectors, there is a dearth of information on how housing type may influence malaria transmission among U5 children in Nigeria. This study assessed the relationship between housing type and malaria prevalence among U5s in Nigeria. Methods: A cross-sectional analysis of the nationally representative 2015 Nigeria malaria indicator survey data was done. A representative sample of 8148 households in 329 clusters was selected for the survey. Children aged 6–59 months in the selected households were tested for anaemia and malaria using the rapid diagnostic test (RDT) and the microscopy. Data were analysed using descriptive statistics, Pearson Chi square (χ2) and logistic regression models at 5% level of significance. Results: The odds of malaria infection was significantly higher among older children aged 24–59 months (aOR = 4.8, CI 2.13–10.99, p < 0.001), and children who lived in houses built completely with unimproved materials (aOR = 1.4, CI 1.08–1.80, p = 0.01). Other predictors of malaria infection include living in a rural area (aOR = 1.5, CI 1.25–1.91, p = 0.01), ever slept under a long-lasting insecticide-treated net (aOR = 1.1, CI 0.26–4.79, p = 0.89) and in a room not sprayed with insecticide (aOR = 1.2, CI 0.64–2.31, p = 0.56). Children who were malaria positive showed a higher prevalence of severe anaemia on RDT (87.6%) and Microscopy (67.4%) than those who were not anaemic (RDT = 31.6%, Microscopy = 12.9%). Conclusions: Non-improved housing predicted malaria infection among U5s in Nigeria. Improved housing is a promising means to support a more integrated and sustainable approach to malaria prevention. Education of the Nigerian people on the role of improved housing on malaria protection and empowerment of the public to adopt improved housing as well as overall enlightenment on ways to prevent malaria infection can help to augment the current malaria control measures among U5 children.